ANTI-RACISM: A STUDY OF THE MAIN CHARACTERS IN THE HELP (2009) NOVEL BY KATHRYN STOCKETT - Iban, Ageline; Sili, Surya; Asanti, Chris (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2019)
The Help is a novel written by Kathryn Stockett and published in 2009. This novel tells about the lives of black maids who were discriminated by the white master around 1960s in Jackson, Mississippi. This research focused on analyzing the anti-racism of the main characters who are Skeeter, Aibileen and Minny. The purpose of this research was to analyze how the main characters’ anti-racism attitude in The Help novel and to analyze why the main characters become anti-racist people. This research is a qualitative research. This research used two theories, the first is Gordon Allport’s prejudice and discrimination theory and the second is social psychology theory. The result of this research showed that the main characters’ anti-racism attitude such as: verbal antagonism, avoidance and segregation. Meanwhile the factors in social psychology that influence the main characters become anti-racist people are identification factors in social psychology, motive, and social characteristic. Novel The Help adalah novel yang di tulis oleh Kathryn Stockett dan terbit pada tahun 2009. Novel ini bercerita tentang kehidupan para wanita pembantu rumah tangga kulit hitam yang didiskriminasi oleh majikan kulit putih sekitar tahun 1960-an di kota Jackson, Mississippi. Penelitian ini fokus pada menganalisa anti-rasisme dari para tokoh utama yaitu Skeeter, Aibileen dan Minny. Tujuan dari penelitian adalah untuk menganalisa bagaimana sikap anti-rasisme dari para tokoh utama dalam novel The Help dan menganalisa mengapa para tokoh utama menjadi seorang yang anti-rasis. Penelitian ini adalah sebuah penelitian kualitatif. Penelitian ini menggunakan dua teori, teori pertama yaitu  teori prasangka dan diskriminasi dari Gordon Allport dan yang kedua yaitu teori psikologi sosial. Hasil penelitian menunjukan sikap anti-rasisme dari para tokoh utama yang melawan sikap rasis yaitu: lisan antagonisme, penghindaran dan pemisahan. Sementara factor-faktor dalam psikologi sosial yang mempengaruhi para tokoh utama menjadi seorang yang anti-rasis yaitu faktor identifikasi dalam psikologi sosial, motif, dan karakteristik sosial.